Impaired Left Atrial Performance Resulting From Age-Related Arial Fibrillation Is Associated With Increased Fibrosis Burden: Insights From a Clinical Study Combining With an in vivo Experiment - Lin, Kai-bin; Chen, Kan-kai; Li, Shuai; Cai, Ming-qi; Yuan, Min-jie; Wang, Yan-peng; Zhang, Xue; Wei, Meng; Yan, Mei-Ling; Ma, Xin-Xin; Zheng, Dong-Yan; Wu, Qi-han; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Atrial fibrillation (AF) is increasingly considered an age-related degenerative disease, whose process is associated with the development of impaired left atrial (LA) performance. However, the subtle dynamic changes of LA performance in AF during aging have yet to be fully elucidated. Atrial fibrosis is a key substrate for the development of AF, but the progression of fibrosis during aging and its relationship with LA dysfunction needs to be further explored. Methods: A total of 132 control individuals and 117 persistent AF patients were prospectively studied. Subjects were further stratified into three age groups（age group-1: under 65 years old, age group-2: between 65 to 79 years old and age group-3: over 80 years old). The two-dimensional speckle tracking imaging was carried out for analyzing the alterations in LA function underlying LA remodeling, while electroanatomic mapping was performed to investigate LA fibrosis burden. In animal study, aged mice and young mice served as research subjects. Echocardiography and histological staining were used to assess LA performance and fibrosis burden, respectively.Results: Echocardiography showed progressive increases in LA dimension and LA stiffness index, and progressive decreases in LA global longitudinal strain and LA strain rates with advancing age in both AF and control cohort, which was more prominent in AF cohort. Electroanatomic mapping showed progressive decrease in mean LA voltage, and progressive increases in LA surface area, LVA% and LA volume with advancing age , while more significant alterations were observed in AF patients. Moreover, GLAS was positively correlated with mean LA voltage, whereas LA stiffness index was negatively related to mean LA voltage. In animal experiment, increased LA size and pulmonary artery dimension as well as longer P-wave duration and more prominent LA fibrosis were found in aged mice.Conclusions:This study provides new evidences of subtle changes in structure and performance of left atrium and their association with atrial fibrosis in both AF and non-AF subjects during physiological aging. In addition, our study also provides normal values for LA structure and performance in both AF and non-AF conditions during aging.These measurements may provide an early marker for onset of AF and LA adverse remodeling.